2016
DOI: 10.4025/actascianimsci.v38i1.29171
|View full text |Cite
|
Sign up to set email alerts
|

<b>Evaluation of digestion procedures in Kjeldahl method to quantify total nitrogen in analyses applied to animal nutrition

Abstract: ABSTRACT. The effects of the salt-to-metal catalyst ratio and amount of digestion mixture on total nitrogen content in different materials using the Kjeldahl method were evaluated. Four samples with low nitrogen contents and four samples with high nitrogen contents were analyzed. The study evaluated two ratios of salt (sodium sulfate) to metal catalyst (copper sulfate) in the digestion mixture (10:1 and 20:1) and three amounts of digestion mixture per sample (1.0, 1.5, and 2.0 g 200 mg -1). There was an intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
1
5
0
5
Order By: Relevance
“…The amount of protein present in Gum Arabic is commonly determined by analysis of the total nitrogen by the Kjeldahl method [43] and multiplying the nitrogen percent by factor 6.6 [21]. The present work showed that nitrogen and protein contents range between (0.27 ̶ 1.78%) and (0.20 ̶ 1.32%) were within the international specifications of Kakamut and Hashab Gums respectively.…”
Section: Discussionsupporting
confidence: 60%
“…The amount of protein present in Gum Arabic is commonly determined by analysis of the total nitrogen by the Kjeldahl method [43] and multiplying the nitrogen percent by factor 6.6 [21]. The present work showed that nitrogen and protein contents range between (0.27 ̶ 1.78%) and (0.20 ̶ 1.32%) were within the international specifications of Kakamut and Hashab Gums respectively.…”
Section: Discussionsupporting
confidence: 60%
“…Shoot dry weights were expressed as total grassland biomass per m 2 . Plant tissue crude protein was determined by Kjeldahl method (Da Silva et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…A ausência de efeito de bateria de análise sobre a recuperação de nitrogênio no padrão HCl-Lisina e para as demais amostras avaliadas sob as diferentes soluções de destilação reitera aspectos de rusticidade do método de Kjeldahl, conforme verificado por outros autores (SILVA et al, 2016;RODRIGUES et al, 2018).…”
Section: Discussionunclassified
“…Tal fato demonstra que, mesmo utilizando-se as soluções de destilação contendo as menores concentrações tanto de AB (20 g/L) quanto dos indicadores VM (12 mL/L) e VB (6 mL/L), a quantidade de N mensurada não sofre alteração. Por outro lado, a ausência de efeitos associados aos fatores principais (concentrações de AB e de indicadores) reitera a ideia de que a quantidade de reagentes utilizada nas diferentes etapas do método de Kjeldahl tem sido acima do necessário, demonstrando a necessidade de estudos objetivando maior eficiência de utilização dos mesmos, conforme observado também em outros trabalhos (SILVA et al, 2016;RODRIGUES et al, 2017).…”
Section: Discussionunclassified
See 1 more Smart Citation